Cryptochrome 1a of tomato mediates long-distance signaling of soil water deficit - D'Amico-Damião, Victor [UNESP]; Dodd, Ian C.; Oliveira, Reginaldo [UNESP]; Lúcio, José C.B. [UNESP]; Rossatto, Davi R. [UNESP]; Carvalho, Rogério F. [UNESP] (Elsevier, 2021)
Although the blue light photoreceptors cryptochromes mediate the expression of genes related to reactive oxygen species, whether cryptochrome 1a (cry1a) regulates local and long-distance signaling of water deficit in tomato (Solanum lycopersicum L.) is unknown. Thus the cry1a tomato mutant and its wild-type (WT) were reciprocally grafted (WT/WT; cry1a/cry1a; WT/cry1a; cry1a/WT; as scion/rootstock) or grown on their own roots (WT and cry1a) under irrigated and water deficit conditions. Plant growth, pigmentation, oxidative stress, water relations, stomatal characteristics and leaf gas exchange were measured. WT and cry1a plants grew similarly under irrigated conditions, whereas cry1a plants had less root biomass and length and higher tissue malondialdehyde concentrations under water deficit. Despite greater oxidative stress, cry1a maintained chlorophyll and carotenoid concentrations in drying soil. Lower stomatal density of cry1a likely increased its leaf relative water content (RWC). In grafted plants, scion genotype largely determined shoot and root biomass accumulation irrespective of water deficit. In chimeric plants grown in drying soil, cry1a rootstocks increased RWC while WT rootstocks maintained photosynthesis of cry1a scions. Manipulating tomato CRY1a may enhance plant drought tolerance by altering leaf pigmentation and gas exchange during soil drying via local and long-distance effects.
Keywords: Abiotic stress; cry1a mutant; Drought; Root-shoot signaling; Solanum lycopersicum L.; Water deficit